Legal Terms in General Dictionaries of English: The Civil Procedure Mystery - Nielsen, Sandro (Lexikos, 2015)
Many general language dictionaries contain specialized terms, including legal terms relating to civil lawsuits. The existing literature provides general discussions of scientific and technical terms in ordinary dictionaries but does not specifically address the inclusion of legal terms. This study examines four general dictionaries of English to see how they treat civil procedure terms used in England and Wales in the light of the change of structure of and terminology used in civil proceedings that took place in 1999. Despite being based on large, up-to-date corpora the dictionaries contain some of the old terms but fail to include the new terms that have been in use for more than 15 years. Why this is the case is a mystery. However, some clues indicate that if they pay more attention to the link between dictionary functions, corpora and the data presented in dictionaries, lexicographers may be able to work in a more focussed way that would likely ensure the inclusion of legal terms as well as terms from other subject fields in general dictionaries. This would also satisfy the needs of users.